Light-harvesting complexes communicate growth and physiology of plants - Md. Sarwar, Jahan; Mainul, Hasan (2017)
Light-harvesting complexes (LHCs) regulate light-controlled energy production during photosynthesis process in plants. The proteins related to LHCs co-ordinate molecules into the light antenna structures. Although, structural information and genes related to the LHCs were studied. There is a gap remaining to certify the function of LHCs on the growth and physiology of plants. In the recent year, LHCs progressively increase the functional activities in the plants, which gain interest and importance to the researchers due to the ability of plants to respond and acclimate to the environmental conditions due to climate changes. To date, information is still being presented regarding the function of LHCs on growth and physiology of plants. This mini-review highlights the improvements made among LHCs on growth and physiological processes of plants through which glutathione (GSH), chlorophyll content, photosynthesis and nonphotochemical quenching act in plants.